PEMANFAATAN TEKNOLOGI INFORMASI SEBAGAI SUMBER BELAJAR GUNA MENINGKATKAN HASIL BELAJAR SISWA - Maimunah (UNISAN JURNAL, 2024)
This exploration plans to decide the utilization of data innovation as a learning asset to further develop understudy learning results in Islamic strict schooling subjects at SMP Muhammadiyah Babat Toman . In this exploration, subjective examination techniques were utilized. Information assortment techniques incorporate perception, meetings and documentation. Information investigation incorporates information assortment, information decrease, and making determinations. In view of the aftereffects of the clarification above, it very well may be reasoned that first, the utilization of data innovation in Islamic strict subjects, educators use picking up utilizing existing mechanical hardware, for example, workstations, LCDs, power focuses and the web. Through data innovation, understudies effectively acknowledge the material introduced by the educator and understudy learning exercises in class are more dynamic, the study hall climate is helpful so that learning is more successful and proficient and doesn’t look tedious. The subsequent educator can use data innovation since he needs to encourage understudies’ delight in Islamic strict subjects. It has been demonstrated that understudies who get material by seeing and hearing will continuously recollect, comprehend and be aware. In this way, there is a unique interest from understudies in concentrating on Islamic strict schooling so it is not difficult to retain the material in light of the understudies’ excitement. high in learning. These discoveries can add to educators in picking the right learning assets as per learning targets, topic, understudy conditions, accessible offices and framework and instructor capacities, in order to make successful figuring out how to accomplish the normal objectives.